The prevalence of symptoms of common mental disorders among professional golfers - Hopley, G.; Murray, A.; MacPherson, A. (International Journal of Golf Science, 2023)
This study assessed; (i) the prevalence of symptoms of mental health disorders among a cohort of professional golfers and (ii) players` views on the mental health support services available to them.